The Susa wreath group Alexanders: The first step in the transformation of an anchor seal to a dynastic emblem - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2019)
A tetradrachm die study of the Susa wreath group (Susa Group 5) of Alexanders (Price 3853-60) attributed to the satrapy of Aspeisas in the period 316/5-312/1 BC, indicates that the coinage should be downdated to the period 311/0-309/8 BC, the earliest coinage of Seleukos from the mint. A newly identified component of the coinage, die linked to the wreath group while bearing an anchor recut over the wreath, represents the first appearance on coinage of what was to become the primary Seleukid dynastic emblem. It sheds light on the origin and timing of placement of Seleukos’s personal insignia, or seal, on his coinage, and its subsequent development into a dynastic emblem.